Post pandemic, the movements of society and public social authority in Peru - Ortiz Fernández, Carolina (2020)
This paper explores some of the factors for which a significant part of the working population did not abide by the social confinement decreed early in Peru. Secondly, the alternatives that are created and offered from social organizations and society movements are investigated in an introductory way, in a post-covid context, in which with the discourse of economic reactivation the elites tend to deepen the precariousness of work, the increase in the marginalized workforce and the growing authoritarian vigilance, as part of global politics, and which in the country is not recent, has existed for several years. All these moving forces suppose a pachacuti, that is to say a radical mutation. A research is approached from the decoloniality of power and gender perspectiva.